(untitled) (Research, Society and Development, 2025)
Working with inclusive education is still a challenge for both teachers and students, so it is necessary to have reflections, debates, and dissemination of knowledge on this subject. However, more focused studies are needed to translate theory into everyday classroom practices. This study aims to review the theme of teaching English to students with Autism Spectrum Disorder (ASD) through academic material available on the internet. Online research on academic sources, in the last ten years, including articles from the SciELO digital library and Google Scholar, was conducted to explore challenges faced by teachers in teaching English to students with ASD, with a focus on basic education and higher education. The articles were selected for their relevance to the topic and their focus on difficulties encountered by teachers and strategies that can help students with ASD. The results indicated that, although the context is completely different, the challenges are similar, the convergence of these studies is mainly due to the need for teacher training, curricular adaptation, methodology and technological resources as tools to facilitate learning. Given these findings, it is hoped that this study will emphasize the importance of further research and investment in inclusive education, particularly in foreign language teaching.